Fuzzy Lyapunov function based stability analysis of hybrid multiple-frequency system with low frequency offshore wind power integration - Ziyue Duan; Yongqing Meng; Tianyi Wang; Boyang Zhao; Xiuli Wang; Xifan Wang (International Journal of Electrical Power & Energy Systems)
Low frequency transmission is gradually becoming a competitive solution for offshore wind power integration. However, the large signal stability issues induced by the low frequency offshore wind power integration have also become a focal point of concern. Thus, this article firstly analyzes the unique impact of integrating low frequency wind power into hybrid multi-frequency system on large signal stability from the perspective of power frequency synchronous generators, using power-angle curves and the equal area criterion. Then, three active power transmission paths for the low frequency transmission system are defined, revealing stability mechanism under varying wind power penetration rate and transmission frequency. Furthermore, the improved fuzzy Lyapunov function method is proposed to calculate the system’s energy function and domain of attraction, reducing the conservativeness of quadratic energy function and eliminating the need for bounded time derivatives of membership function. On top of that, by introducing the concepts of large signal stability margin and sensitivity, it presents the quantitative optimization scheme for enhancing system stability. Additionally, the selection criterion from the stability perspective for optimal transmission frequency is proposed. Finally, simulations and experimental results confirm the effectiveness of the theoretical analysis.